EVALUASI PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN KABUPATEN BUTON TAHUN 2014 - Alimuddin Matu (Master of Public Administration, Universitas Slamet Riyadi, 2015)
Musrenbang an assessment of the most important results of theproposed program priorities of the community. Musrenbang is a forum toexpress the aspirations of the people, in the development process thatwill be implemented by the government. Musrenbang is the process ofadvancing every area ranging from rural/village, district,district/municipal, provincial and central.This study aims to determine the Musrenbang Buton 2014. This studyused a qualitative approach perspective. Qualitative research conductedin the state of nature (natural setting). The approach used is aphenomenological approach (post-positivist), which is described with theunderstanding than expected, with the working hypothesis thanpengujiann strict hypothesis, and the reciprocal relationship between theresearcher and the object of study rather than a separate observationon the part of the analyst.Implementation Musrenbang in Buton has gone through various stages,the procedures for making, Control, and Evaluation of theImplementation of the Regional Development Plan. In generalMusrenbang Buton can run well, although not in spite of obstacles andbarriers, both the organizers and of the implementation. From theorganizers, BAPPEDA as agency responsible for the implementation ofplanning forums without any significant obstacles.Musrenbang can be a strategic activity that is expected to accommodateinput of citizens in local development planning as a form of publicparticipation in the development of bottom-up to be harmonized with theactivities of the development programs of the government that is topdown. Musrenbang should be a strategic forum, however, from year toyear tends to decline in quality due to the emergence of communitysaturation.BAPPEDA as a planning agency should facilitate the establishment of afacilitator musrenbang at village / district and sub-district, preceded by atraining/ technical briefing before the circuit musrenbang implemented.In addition, the need for involvement of academics, community leaders,NGOs, and relevant stakeholders in the formulation of a preliminarydraft RKPD through public consultation into the draft RKPD as materialMusrenbang District.Keywords: Evaluation, Musrenbang, BAPPEDA